2006
DOI: 10.1152/ajpregu.00139.2006
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by 17β-estradiol in bivalve hemocytes

Abstract: .-In mammals, estrogens have dose-and cell-type-specific effects on immune cells and may act as pro-and anti-inflammatory stimuli, depending on the setting. In the bivalve mollusc Mytilus, the natural estrogen 17␤-estradiol (E2) has been shown to affect neuroimmune functions. We have investigated the immunomodulatory role of E 2 in Mytilus hemocytes, the cells responsible for the innate immune response. E2 at 5-25 nM rapidly stimulated phagocytosis and oxyradical production in vitro; higher concentrations of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 50 publications
5
43
0
Order By: Relevance
“…The use of GF-109203X and/or Gö6976, in order to inhibit each PKC isoforms in 17b-estradiol treated cells, revealed the important role of PKC in the adhesion of hemocytes, thus verifying previous data concerning a PKC-mediated immunomodulation in hemocytes of mussels [24,57]. Moreover, Ottaviani et al [64] suggested that IL-8 triggers conformational changes, induces chemotaxis and increases phagocytic activity in M. galloprovincialis hemocytes through PKA and PKC pathway.…”
Section: Hemocyte Adhesion To Ecm Proteins In 17b-estradiol-treated Hsupporting
confidence: 70%
See 1 more Smart Citation
“…The use of GF-109203X and/or Gö6976, in order to inhibit each PKC isoforms in 17b-estradiol treated cells, revealed the important role of PKC in the adhesion of hemocytes, thus verifying previous data concerning a PKC-mediated immunomodulation in hemocytes of mussels [24,57]. Moreover, Ottaviani et al [64] suggested that IL-8 triggers conformational changes, induces chemotaxis and increases phagocytic activity in M. galloprovincialis hemocytes through PKA and PKC pathway.…”
Section: Hemocyte Adhesion To Ecm Proteins In 17b-estradiol-treated Hsupporting
confidence: 70%
“…Moreover, integrins orchestrate multiple functions including proliferation, differentiation, gene expression, changes in intracellular pH, apoptosis and death [17,18]. Estrogens, such as 17b-estradiol (E 2 ), are among the endocrinedisrupting compounds and exert a broad spectrum of activities on a wide range of cells and tissues [19e22], among these the immune system of marine invertebrates [23,24]. 17b-estradiol is commonly present in mussel gonads and plays a major role in sexual differentiation, gonad development and oocyte growth [25].…”
Section: Introductionmentioning
confidence: 99%
“…This route of exposure, that allows for direct administration of estrogens into the animal open circulatory system leading to distribution from the blood (hemolymph) to the tissues, including the hepatopancreas, has been largely utilised for evaluating the effects of natural and environmental estrogens in bivalve molluscs (Gagnè et al, 2001;Canesi et al, 2005Canesi et al, , 2006Canesi et al, , 2007Le Curieux-Belfond et al, 2005;Gauthier-Clerc et al, 2006;. In Mytilus sp., exogenous E 2 added to the seawater (200-2000 ng/l) is taken up and progressively metabolised (within 7 days) to an esterified, inactive form that is stored in the tissues, this indicating that mussels can tightly regulate the concentration of free E 2 (Janer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In bivalves, direct administration into the blood (hemolymph) by injection into the adductor muscle sinus has been widely utilised for identifying the possible targets of both natural and environmental estrogens (Gagnè et al, 2001;Canesi et al, 2005Canesi et al, , 2006Canesi et al, , 2007Le Curieux-Belfond et al, 2005;GauthierClerc et al, 2006;. The concentrations of BPA (ng/g dry weight/mussel) were in the same range as those previously shown to affect mussel immune parameters in the same experimental conditions (Canesi et al, 2005) and comparable to environmental exposure levels (Pojana et al, 2004 A c c e p t e d M a n u s c r i p t 6…”
Section: Page 4 Of 32mentioning
confidence: 99%
See 1 more Smart Citation